EFL/ESL Tertiary-Level Learners are No Longer Required to Repeat the Same Dialogues in Speaking Classes: A Case Study from Thai University - Samaranayake, Sarath Withanarachchi; Kositchaivat, Sunneeta; Prasansapah, Soranabordin (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
Over the past few decades, there has been a growing recognition of the positive impact of role-plays involving single events on the speaking skills of EFL learners in various teaching contexts across the globe. However, the effectiveness of role-plays involving sequential events in enhancing the oral proficiency of tertiary-level EFL learners remains unexplored. Therefore, this study aimed to determine whether role-plays involving sequential events were more effective than those involving single events in promoting the oral proficiency of tertiary-level EFL learners. This study employed a pretest-post-test research design and randomly selected two study groups (Treatment: N = 38 and Comparison: N = 38) using purposive sampling techniques. The treatment group was taught using role-plays involving sequential events, while the control group was instructed with role-plays involving single events for one semester. Data was collected through pre and post-tests, intervention tools, and focused group interviews and analyzed using descriptive and inferential statistical tests. The findings indicated that the treatment group, which practised role-plays involving sequential events, demonstrated more significant improvement in speaking proficiency than the control group, which used single events. Based on these positive outcomes, this study suggests that incorporating role-plays involving sequential events into EFL instruction can significantly enhance tertiary-level learners' speaking proficiency. Teachers and educators in the field of EFL/ESL should consider using sequential event role-plays to improve oral communication skills among learners. This approach can be particularly effective in Thai tertiary education, and the results contribute to the discussion on innovative teaching strategies.